THE PERFORMANCE OF VILLAGE-OWNED ENTERPRISES (BUMDES) IN IMPROVING THE COMMUNITY ECONOMY - Samahudin (UIN Mataram, 2023)
Institutional performance of BUMDES in running an internal business by serving the needs ofcommunity members such as basic needs, rental of goods, managing tourist parks, selling localproducts, and others, with low risk so that it can run smoothly and sustainably as expected.BUMDES which grows from social solidarity and local wisdom is quite strong and sustainablethis is due to local wisdom that is full of local products, which is a factor that greatly affects thedurability and sustainability of BUMDES